A Review of Cloud Manufacturing: Issues and Opportunities - Abd Rahman, M.N.; Medjahed, B.; Orady, E.; Muhamad, M.R.; Abdullah, R.; Jaya, A.S.M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Cloud Manufacturing (CM) is the latest manufacturing paradigm that enables manufacturing to be looked upon as a service industry. The aim is to offer manufacturing as a service so that an individual or organization is willing to manufacture products and utilize this service without having to make capital investment. However, industry adoption of CM paradigm is still limited. This paper compared the current adoption of CM by the industry with the ideal CM environment. The gaps between the two were identified and related research topics were reviewed. This paper also outlined research areas to be pursued to facilitate CM adoption by the manufacturing industry. This will also improve manufacturing resource utilization efficiencies not only within an organization but globally. At the end, the cost benefits will be passed down to end customer.